The Effect of Service and Product Quality on The Purchase Decision of Purebred Chicken Eggs with The Level of Education as a Moderation Variable - Fata Alfan Marufi; Muchammad Saifuddin (Dinamis : Journal of Islamic Management and Bussiness, 2022)
This study aims to test and find out the effect of service and product quality on the purchase decision of purebred chicken eggs. In addition, the purpose of this study is to determine the influence of moderation in education levels on the influence of service and product quality on the purchasing decision of purebred chicken eggs. This research uses a quantitative approach with the method of distributing questionnaires. The population of this study was consumers of purebred chicken eggs in Ringinanyar village with a sample of 320 respondents. Data analysis was performed in this study using the SPSS 23.0 application for windows. The results of the analysis showed that the service had a significant effect on the decision to purchase purebred chicken eggs. Product quality has a significant effect on the decision to purchase purebred chicken eggs. Service and product quality simultaneously affect the purchasing decision of purebred chicken eggs. The level of education does not moderate the effect of service on purchasing decisions. The level of education does not moderate the influence of product quality on purchasing decisions. With the results of this study, it is hoped that it can be an input and evaluation material for purebred chicken egg sellers, especially in Ringinanyar village so that the sale of purebred chicken eggs is more optimal.